Uji sifat fisik repelan minyak atsiri kombinasi rimpang temulawak dan rimpang jahe basis cold cream - Siti Fatmawati Fatimah; Wahyu Widyaningsih; Azis Ikhsanudin (Universitas Ahmad Dahlan, 2017)
Ginger Rhizome (Zingiber officinale Rhizome Roxb. Rhizome) and Javanese Turmeric Rhizome (Curcuma xanthorrhiza roxb. Rhizome) contain essential oils that can serve as a repellent. In order to cut the cost and irritating nature of ginger essential oil, essential oils of Javanese Turmeric had been combined. Cold cream base has more oil phase that can improve the ability of essential oils binding. Those bases are expected to increase the effect of repellent. Hence, related to repellan effect, the physical properties test of essential oils must be done to ensure purity and quality. Before performing repellent effects test, a physical properties test to obtain the best formula, i.e., a formula that can be applied topically with ease and comfort when it used. Essential oil of ginger rhizome and javanese turmeric rhizome are isolate by water and steam distillation methods and tested for physical properties, which consists of organoleptic test, refractive index and specific weight. Repellent made in different concentrations, that are 2% v/w, 5% v/w, 10% v/w, 15% v/w, 20% v/w, and 25% v/w, then performed a test of the power spread, sticky ability, and viscosity. The higher concentration of essential oil's cause wider spread ability, but smaller viscosity and stick ability. The selected formula is a formula with 25% w/v concentration, because it has wider spread ability and smaller viscosity so the repellent just need a little effort to rub with smaller stick ability so it's easy to be clean.